Fatty acid profiles of cultured Hippocampus hippocampus trunk muscles and potential nutritional value - Cabral, Ana Elisa; Rey, Felisa; Domingues, M. Rosário; Cabral, Miguel; Planas, Miquel; Palma, Jorge; Calado, Ricardo (Frontiers in Marine Science, 2023)
Syngnathids (seahorses, pipefishes and seadragons) are an attractive resource for Traditional Chinese Medicine (TCM). Despite few scientific studies supporting seahorse nutritional benefits, they are believed to possess medicinal properties that enhance human health. The European short-snout seahorse Hippocampus hippocampus is classified as Data Deficient by the IUCN Red List of Threatened Species. Nevertheless, there are increasing records of this species being illegally captured and traded to supply TCM. This study investigated the fatty acid (FA) profiles of the trunk muscles of cultured female and male H. hippocampus, to assess sex and intraspecific variation, as well as their potential nutritional value. The contents of crude lipid (4.05 ± 2.15% dry weight, DW in females and 2.82 ± 1.48% DW in males) and phospholipid (8.23 ± 3.34 μg mg−1 DW in females and 7.91 ± 2.36 μg mg−1 DW in males) were not significantly different between the two sexes. The absolute FA compositions of H. hippocampus trunk muscles revealed higher mean values for FA 16:0, 18:0, 18:1 n-9 and 22:6 n-3 (DHA), in both female (2.82 ± 1.11, 1.81 ± 0.89, 0.90 ± 0.41 and 0.93 ± 0.35 μg mg−1 DW, respectively) and male specimens (1.99 ± 0.95, 1.52 ± 0.78, 0.74 ± 0.44 and 0.80 ± 0.41 μg mg−1 DW, respectively). In terms of FA classes, saturated fatty acids (SFA) showed the highest absolute value of the total pool of FA, for both sexes (4.73 ± 1.94 μg mg−1 DW in females and 3.58 ± 1.76 μg mg−1 DW in males). Males tended to exhibit a more suitable profile for human nutrition, displaying a lower atherogenic index (AI) and thrombogenic index (TI). The relative composition of H. hippocampus trunk muscles followed the patterns of seahorse species valued in TCM, with DHA ranking amongst the PUFA with higher mean relative abundances (12.0% of total FA). While seahorse FA profiles may be of interest in terms of their nutritional value for humans, only specimens originating from sustainable production practices should be traded and the conservation of their populations in the wild should continue to be a global priority.